Sterically stabilized cyclopropenonophanes and an electronically stabilized cyclopropenethionophane: syntheses, structural properties, and reactivity - Werz, Daniel B.; Schuster-Haberhauer, Andreea; Gleiter, Rolf; Rominger, Frank (Organic letters, 2005)
The syntheses of sterically stabilized cyclopropenonophanes as well as an electronically stabilized cyclopropenethionophane are reported, and their molecular structures in the solid state are elucidated. The sulfur of the CS moiety in cyclopropenethiones was shown to react as a nucleophile. Temperatures of more than 240 °C favor the extrusion of CO in the cyclopropenonophane to afford an α,α‘-tetramethyl-substituted cyclodiyne.
Gesehen am 06.11.2020